Effect of electrode design and operating condition on performance of hydrogen alkaline membrane fuel cell. (1st December 2016) - Deng, Hao; Wang, Dawei; Wang, Renfang; Xie, Xu; Yin, Yan; Du, Qing; Jiao, Kui
Highlights: AAEMFCs were tested with various electrode designs and operating conditions. Theoretical analysis is carried out for these experimental conditions. MPL, anode pressurization, high ionomer content and gas humidity are favorable. MPL and anode pressurization are beneficial to water balance. Increased water amount in CCL reduces both mass transport and ohmic losses. Abstract: Hydrogen alkaline anion exchange membrane (AAEM) fuel cells are fabricated and tested, by measuring the output current densities at various cell voltages with a step change of 0.1 V, under various ionomer contents in catalyst layer (volume fraction, 0.07, 0.21 and 0.50), inlet gas relative humidities (100%, 86% and 70%), anode back pressures (1.0, 1.01 and 1.02 atm) and with/without insertion of micro porous layer (MPL). The corresponding theoretical analysis is also carried out, to clarify the factors that determine these experimental results. The experimental results show that high ionomer content, inlet gas humidity, slight anode pressurization and insertion of micro porous layer (MPL) are favorable. Since insufficient water supply (not oxygen) in cathode contributes to the major performance losses and low limiting current density, it is expected that properly increasing the water amount in cathode could effectively improve the membrane hydration, but not to causes considerable negative effect to cell performance.